КОРРЕЛЯЦИОННЫЕ ВЗАИМОСВЯЗИ УРОВНЕЙ И ТИПОВ СОЦИАЛИЗАЦИИ С КОММУНИКАТИВНЫМИ КАЧЕСТВАМИ ЛИЧНОСТИ УЧАЩИХСЯ - Клычева, З.П. (SCIENCE and SOCIETY, 2025)
This article talks about the correlation between the levels and types of socialization with the communicative qualities of the personality of adolescent and early youth students from the 5th to the 11th grades, studying in schools with different languages of instruction.